Mempersiapkan Pendidik Masa Depan di Era Kecerdasan Buatan: Pengalaman Calon Guru Sekolah Dasar dengan Aplikasi Generatif AI: Penelitian - Muhammad Ikhlas; Lutfia Yasmin; Delvia Muharramah; Kuswanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examine the exposure, usage, and preferences of primary school teacher education students toward Generative AI (GenAI) applications, as well as the relationship between demographic characteristics and participation in AI-related training and seminars. A descriptive quantitative approach was employed, with 155 respondents using a closed-ended questionnaire. Data were analyzed using descriptive statistics and chi-square tests. The results show that ChatGPT is the most popular and frequently used application, followed by Google Gemini and Perplexity AI. No significant relationship was found between gender or semester and participation in AI-related events. These findings reflect students’ early engagement with GenAI technologies in education.